2021
DOI: 10.1002/csc2.20588
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic diversity and association mapping for seed weight and size in vegetable soybean germplasm

Abstract: Edamame is a vegetable‐typesoybean [Glycine max (L.) Merr.] with large seed size, typically twice that of commodity soybean. Understanding the genetic diversity among large‐seeded germplasm as well as the genetic variation for seed size in the germplasm pool is important for edamame breeding. The objectives of this study were to analyze the genetic diversity of 343 edamame soybean accessions and 36 breeding lines, and to identify quantitative trait loci (QTLs) associated with seed weight (SW), seed volume (VOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Here, the average heterozygosity rate was 11.99% in these four cultivars. These results were consistent with the previous similar studies [ 7 , 8 , 15 ], and showed the difference between vegetable and grain soybeans at the genome level. It is speculated that the SNP heterozygosity is closely related to the parental characteristics.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Here, the average heterozygosity rate was 11.99% in these four cultivars. These results were consistent with the previous similar studies [ 7 , 8 , 15 ], and showed the difference between vegetable and grain soybeans at the genome level. It is speculated that the SNP heterozygosity is closely related to the parental characteristics.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, 16 and 10 genes were associated with sucrose and starch metabolic processes, respectively, some of which might play a role in sucrose and starch metabolism. A number of SNPs are reportedly associated with sucrose and protein contents [ 8 , 26 , 27 ]. Once confirmed, the differences could provide an insight into breeding selection of vegetable soybean as well as the loss of function of genes that may have a key role in grain soybean.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These landraces contain rich genetic resources, which are the foundation for the promotion and development of the characteristic soybean industry in this locality. Therefore, it is a current area of concern in terms of how to transform this potential advantage into a practical advantage [9,10,14,15].…”
Section: Introductionmentioning
confidence: 99%